Connected Disjunctive Domination in Graphs (European Journal of Pure and Applied Mathematics, 2025)
A set $S$ of vertices of a graph $G$ is a disjunctive dominating set if for every $v\in V(G)\setminus S$, $v$ is adjacent to a vertex in $S$ or $S$ contains two vertices each of distance two from $v$. A disjunctive dominating set $S$ is a connected disjunctive dominating set if $\langle S\rangle$ is connected.  In this paper, we study the concept of connected disjunctive dominating set.
Keywords: Connected Domination; disjunctive domination; join; corona; lexicographic product